Kasus Argumen Inti Verba Bahasa Muna di Sulawesi Tenggara - Alu, La; Sarmadan, Sarmadan (GERAM: Gerakan Aktif Menulis, 2023)
The Muna language serves as both a social language and a means of communication within the Muna sociocultural area, actively used and mastered by its speakers. The objective of this study is to uncover linguistic facts, specifically those related to the core argument cases of verbs in the Muna language. The research employs a descriptive method aimed at providing an accurate description of the data, characteristics, and relationships of the phenomena under investigation. The research findings reveal various verb core argument cases in the Muna language, including: (a) Stative verb core argument cases, which encompass (i) basic stative verb core argument cases, (ii) stative experiential verb core argument cases, (iii) stative verb core argument cases involving ownership, and (iv) core argument cases of locative stative verbs. (b) Core argument cases for process verbs, which consist of (i) basic process verb core argument cases, (ii) process experience verb core argument cases, (iii) process verb core argument cases involving ownership, and (iv) core argument cases of locative process verbs. (c) Action verb core argument cases, which include (i) basic action verb core argument cases, (ii) action experience verb core argument cases, (iii) action verb core argument cases involving possession, and (iv) core argument cases of locative action verbs.